Ecology of the benthic mucilage-forming microalga Chrysophaeum taylorii in the W Mediterranean Sea: Substratum and depth preferences. (5th August 2015) - Caronni, Sarah; Bresciani, Alessia; Delaria, Maria Anna; Meloni, Federico; Navone, Augusto; Panzalis, Pieraugusto; Heimann, Kirsten; Ceccherelli, Giulia
Abstract: Chrysophaeum taylorii Lewis and Bryan (Pelagophyceae) is an allochthonous benthic microalga recently recorded in the Mediterranean Sea where it is spreading quickly. Although this species secretes mucilage which is seriously affecting marine communities, it has been scarcely studied and no information on its ecology is available yet. We present the results of a five year study aimed to increase knowledge on substratum and depth preferences of this bloom-forming microalga with special emphasis on its colonisation efficiency. Three separate field experiments established that cell abundances of Chrysophaeum taylorii were significantly lower on macroalgae, mollusc shells and sand than on hard granitic substrata, where the microalga settled efficiently and proliferated immediately independently of the colonisation level of the substratum (bare vs colonised) and the substratum stability (mobility) (cobbles vs rocks). Furthermore, C . taylorii abundance (density) decreased with depth >2 m, showing it prefers shallow waters in which it is able to resist to high light intensities. These results offer some important insights into the ecology of this bloom-forming microalga that will contribute to the planning of future research and strategies for management of bloom events. Graphical abstract: Highlights: Chrysophaeum taylorii is an allochthonous microalga producing detrimental mucilage. Three manipulative experiments along the Sardinian coasts (Mediterranean Sea) were done. The effect of substratum and depth on C . taylorii blooms was tested. Substratum properties can seriously affect C . taylorii development. Depth is another important factor in regulating the distribution of C . taylorii cell density.